Effects of melengesterol acetate on inflammatory response during Mannheimia haemolytica challenge - Corrigan, M.E.; Drouillard, James S.; Spire, M.F.; Moser, Daniel W.; Higgins, James J.; Loe, E.R.; Fox, J.T.; Minton, J. Ernest; Depenbusch, Brandon E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Previous trials conducted at Kansas State University demonstrated that melengesterol acetate (MGA) increased growth rates and tended to reduce chronic sickness in heifers naturally challenged with undifferentiated bovine respiratory disease. Our study was conducted to gain further insight into the mode of action of MGA. Crossbred heifers (n=47; 511 lb) were used to evaluate effects of MGA on lung pathology and markers of inflammation in cattle after an intrabronchial Mannheimia haemolytica challenge. On day 0, cattle were assigned to diets (54% concentrate) that provided 0 or 0.5 mg MGA per heifer daily. On day 14 each heifer was intrabronchially inoculated with M. haemolytica. Blood samples were collected from each heifer immediately before inoculation and 12, 24, 48, 72, 96, 120, and 138 hours after inoculation. Heifers were then euthanized for postmortem examination. After the challenge, heifers fed MGA had greater numbers of neutrophils and white blood cells, as well as greater serum haptoglobin and fibrinogen concentrations. The incidence of post-challenge lung lesions was greater in heifers fed MGA, and lung lesion scores tended to be more severe in heifers fed MGA, compared with those of controls. These data indicate that MGA does not reduce inflammation in heifers 138 hours after M. haemolytica challenge, suggesting that there are other modes of action for the beneficial effects on growth and reduction of chronicity in feedlot heifers.
Keywords: Beef; Melengesterol acetate; Mannheimia haemolytica